2007
DOI: 10.1358/mf.2007.29.3.1092095
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin induces cell-cycle G1 arrest through elevating Cdk inhibitors p21 and p27 in human hepatoma cell line (HepG2)

Abstract: Quercetin is a flavonoid ubiquitously found in nature. The therapeutic effect of quercetin on human hepatoma cell line (HepG2) was evaluated in this study. Various groups were incubated with different doses of quercetin for 12-, 24-, 48- and 72-h time duration and compared with control groups. Dose- and time-dependent inhibition in HepG2 proliferation was found with quercetin treatment. At 48 h of incubation, 61.78% of the cells were arrested at G(1) phase with 25 microM/l quercetin while 89.62% were arrested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 0 publications
2
43
1
3
Order By: Relevance
“…This is further supported by decreased levels of CDK2, CDK6, cyclin D, cyclin E, cyclin A, and pRb accompanied by induction of p21 and p27. Accordingly, Mu and colleagues (35) demonstrated that in HepG2 human hepatoma cells, quercetin blocks cell-cycle progression at G 1 phase and exerts this effect through the p21, p27, and p53 increase. p21 is an important growth arrest mediator and a CDK activity regulator, inhibiting cell entry into G 1 phase in response to DNA damage and blocking the reentry of G 2 cells into S phase by blocking cyclin E-CDK2-mediated Rb phosphorylation (36).…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by decreased levels of CDK2, CDK6, cyclin D, cyclin E, cyclin A, and pRb accompanied by induction of p21 and p27. Accordingly, Mu and colleagues (35) demonstrated that in HepG2 human hepatoma cells, quercetin blocks cell-cycle progression at G 1 phase and exerts this effect through the p21, p27, and p53 increase. p21 is an important growth arrest mediator and a CDK activity regulator, inhibiting cell entry into G 1 phase in response to DNA damage and blocking the reentry of G 2 cells into S phase by blocking cyclin E-CDK2-mediated Rb phosphorylation (36).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that flavonoids modify various cellular functions, such as proliferation [7], apoptosis [8], and transcription and/or translation [9], in manners dependent on or independent of its antioxidant properties. In addition, it has been reported that some flavonoids and flavonoid derivatives affect ion transport [10-14, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studied have revealed that flavonoids modulate various cellular functions, such as cell cycle progression [7], apoptosis [8], and gene expression [9]. In addition, our previous studies have indicated that some flavonoids stimulate ion transport [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Rutin may be useful for the prevention and treatment of colorectal carcinogenesis [13]. Quercetin could be a constituent of chemotherapeutic drugs for the treatment of prostate and skin cancer, because it shows a growthinhibitory effect to tumorigenic cells [14,15]. Although some in vivo studies reported genotoxic and carcinogenic effect of quercetin in rats [16,17], quercetin is not classifiable as carcinogenic to humans [18].…”
Section: Introductionmentioning
confidence: 99%